Is the fourth port routinely required for laparoscopic cholecystectomy? Our three-port laparoscopic cholecystectomy experience. (November 2016) - Ciftci, A.; Yazicioglu, M.; Tiryaki, C.; Turgut, H.; Subasi, O.; Ilgoz, M.; Civil, O.; Yildiz, S.
Abstract Background There have been many changes in number and place of trocars that have been described, since the first laparoscopic cholecystectomy (LC), but, in fact, all authors agree that laparoscopic procedure is accepted as gold standard. However, four trocars use in standard laparoscopic cholecystectomy, it has been argued that the fourth port is not necessary for grasping fundus of gallbladder so as to expose Calot's triangle. The aim of this study is to establish the safety of three-trocar LC in symptomatic gallbladder disease and also to determine the ratio of technical requirements of the fourth trocar. Methods Between August 2010 and January 2016, 291 cases were operated in Kocaeli Derince Education and Research Hospital, department of general surgery for symptomatic gallbladder disease with three-port LC, and their records were examined retrospectively. Results Two hundred and twenty patients were female (75.6 %) and seventy one (24.4 %) were male. Two hundred and eighteen of two hundred and ninety-one cases (74.92 %) were operated with three- port LC in a secure way. In seventy-three cases (25.08 %), one more port was needed to use. Mean operative time was 33.76 ± 11:18 min. (15–90 min). In these cases, major complications, such as main bile duct injury or bile leakage, that may increase the mortality and morbidity, did not occur. Only in one case (0.34 %) postoperative bleeding was seen from the liver bed, which was required exploration. Conclusion We concluded that in experienced hand, LC with three ports is safe and feasible technique if it is not endanger the course of the surgery.